Analisis Eufemisme Dan Disfemisme Pada Judul Berita Online Tribunsumsel.com (Edisi Juni-Juli 2022) - Kartika Oktaviani; Nuraida; Ahmad Harun Yahya (CV. ITTC INDONESIA, 2023)
This thesis is entitled, “Analysis of Euphemisms and Dysphemisms in Online Media News Headlines Tribunsumsel.com”. The background of news headlines in online media that are carelessly made just to attract readers without using language style becomes the author’s concentration.Euphemism and dysphemisms are language styles used by journalist. Expressions with subtle meanings are euphemisms. Expressions with crude or rude meanings are dysphemisms. The lexical semantic approach is the focus of the author because it can describe the meaning of words found in the dictionary. The purpose of this study is to describe the forms and benefits of the use of euphemisms and dysphemisms as well as writing standards in online media headlines Tribunsumsel.com for the periode June-Jully 2022. The research produces descriptive qualitative data with data used in the form of words. The result of this study show that there is the use of euphemism in the form of words and phrases with a total of 7 data and dysphemism on the form of words with a total of 6 data. As well as Tribunsumsel.com which has its own little writing standards.